Impact of negative pressure wound therapy on enteroatmospheric fistulation in the septic open abdomen. (20th September 2022) - Kalaiselvan, Ramya; Slade, Dominic A. J.; Soop, Mattias; Burnett, Hugh; Lees, Nicholas P.; Anderson, Iain D.; Lal, Simon; Carlson, Gordon L.
Abstract: Aim: The effect of negative pressure wound therapy (NPWT) on the pathogenesis and outcome of enteroatmospheric fistulation (EAF) in the septic open abdomen (OA) is unclear. This study compares the development and outcome of EAF following NPWT with that occurring in the absence of NPWT. Methods: Consecutive patients admitted with EAF following abdominal sepsis at a National Reference Centre for intestinal failure between 01 January 2005 and 31 December 2015 were included in this study. Patients were divided into two groups based on those that had been treated with NPWT and those that had not (non‐NPWT) and characteristics of their fistulas compared. Clinical outcomes concerning nutritional autonomy at 4 years and time to fistula development, size of abdominal wall defect and complete fistula closure were compared between groups. Results: A total of 160 patients were admitted with EAF following a septic abdomen (31‐NPWT and 129‐non‐NPWT). Median (range) time taken to fistulation after OA was longer with NPWT (18 [5–113] vs. 8 [2–60] days, p = 0.004); these patients developed a greater number of fistulas (3 [2–21] vs. 2 [1–10], p = 0.01), involving a greater length of small bowel (42.5 [15–100] cm vs. 30 [3.5–170] cm, p = 0.04) than those who did not receive NPWT. Following reconstructive surgery, nutritional autonomy was similar in both groups (77% vs. 72%) and a comparable number of patients were also fistula‐free (100% vs. 97%). Conclusions: Negative pressure wound therapy appears to be associated with more complex and delayed intestinal fistulation, involving a greater length of small intestine in the septic OA. This did not, however, appear to adversely affect the overall outcome of intestinal and abdominal wall reconstruction in this study.